Generative Anger: From Social Enterprise to Antagonistic Economies. Issue 3 (2nd July 2020) - North, Peter; Nowak, Vicky; Southern, Alan; Thompson, Matt
Abstract : This essay offers conceptual development for thinking diverse economies in terms of their relationship to antagonism. Rather than seeing antagonism as unhelpfully fueling capitalocentric thinking, the essay argues that antagonism can usefully recognize and engage with problematic forms of power and domination. Building on calls for a closer engagement of community-economies thinking with wider anticapitalist praxis, the essay explores how social and solidarity economy (SSE) practices sometimes reproduce, sometimes challenge, and sometimes build alternatives to forms of power that attempt to shape, obstruct, and obliterate attempts to create better worlds. The essay develops conceptualizations of social enterprise, the social economy, and solidarity economies before offering the novel concept of the antagonistic economy, arguably a site from which angry opposition to constraining power relations can generate a more productive politics of possibility. The conception of the antagonistic economy is developed by discussion of taking back labor through recovered factories and land through community land trusts.